Spike, Mike, slackers & dykes : a guided tour across a decade of American independent cinema - Pierson, John (University of Texas Press, 2014)
The legendary figure who launched the careers of Spike Lee, Michael Moore, and Richard Linklater offers a no-holds-barred look at the deals and details that propel an indie film from a dream to distribution.